New Opportunities and Untapped Scientific Potential in the Abyssal Ocean - Marlow, Jeffrey J.; Anderson, Rika E.; Reysenbach, Anna-Louise; Seewald, Jeffrey S.; Shank, Timothy M.; Teske, Andreas P.; Wanless, V. Dorsey; Soule, S. Adam (Frontiers in Marine Science, 2022)
The abyssal ocean covers more than half of the Earth’s surface, yet remains understudied and underappreciated. In this Perspectives article, we mark the occasion of the Deep Submergence Vehicle Alvin’s increased depth range (from 4500 to 6500 m) to highlight the scientific potential of the abyssal seafloor. From a geologic perspective, ultra-slow spreading mid-ocean ridges, Petit Spot volcanism, transform faults, and subduction zones put the full life cycle of oceanic crust on display in the abyss, revealing constructive and destructive forces over wide ranges in time and space. Geochemically, the abyssal pressure regime influences the solubility of constituents such as silica and carbonate, and extremely high-temperature fluid-rock reactions in the shallow subsurface lead to distinctive and potentially unique geochemical profiles. Microbial residents range from low-abundance, low-energy communities on the abyssal plains to fast growing thermophiles at hydrothermal vents. Given its spatial extent and position as an intermediate zone between coastal and deep hadal settings, the abyss represents a lynchpin in global-scale processes such as nutrient and energy flux, population structure, and biogeographic diversity. Taken together, the abyssal ocean contributes critical ecosystem services while facing acute and diffuse anthropogenic threats from deep-sea mining, pollution, and climate change.